(untitled) (GEOmedia, 2016)
The Transport of Dangerous Goods by Road - DGT – can be a source of risk for the community and the environment. This research, part of the Strategic Interreg Italy - Switzerland Project DESTINATION, proposes a model for ranking portions of an area through the use of indicators representing the areas affected by the criticalities related to an incident that involving vehicles carrying dangerous goods. The model is thus a decision support tool able to identify and plan mitigation measures both from the infrastructural side and from the management side (regulation).